Vícegenerační rodinný dům - Lepš, Jiří (Vysoké učení technické v Brně. Fakulta stavební, 2012)
Téma bakalářské práce je novostavba vícegeneračního rodinného domu v Náchodě. Dispoziční řešení je uzpůsobeno do dvou bytových jednotek. Objekt je zasazen do mírně svažitého terénu. Má dvě nadzemní a jedno podzemní podlaží. Budova je navržena ze systému POROTHERM. Konstrukce střechy je plochá jednoplášťová.

The theme of bachelor´s thesis is new construction of multigenerational family house in Nachod. The layout is designed in two residential units. The building is set in gently sloping terrain. It has two above ground and one underground floor. The building is designed from the system POROTHERM. The roof is flat with single casing.
Multigenerational family house
Keywords: Rodinný dům; vícegenerační; Family house; miltigenerational